The Development of corporate environmental Responsibility of the oil and gas Business in the Transition to «green» Economy - Tatyana Vasilievna Alexandrova (Управленческое консультирование)
The reorientation of national socio-economic systems on the principles of sustainable development necessitates the study of present condition and prospects of development of corporate environmental responsibility of business under the concept green economy. The oil and gas industry took a leading share the gross domestic product and exports Russia, while providing increased operational stress on the environment. It is therefore important to increase the involvement of the oil and gas business in solving global environmental problems, to enhance the transition to new forms of corporate environmental responsibility, adequate modern goals of social development.The aim of the study is the systematization of directions and principles for the development of environmentally responsible oil and gas business in the context of the transition to a green economy. The methodological basis of the research is comparative, statistical and scoring methods.In the work of an analysis of the model of corporate environmental responsibility of enterprises in conditions of "brown" and "green" economy, presented the results of studies of environmental activities of oil companies in Russia. Perspective directions of development are formulated environmental liability of the oil and gas business in the context of more full conformity with the principles of "green" economy, as well as environmental standards and social organizations.Materials contained in this article may complement the theoretical and practical basis of decisions aimed at sustainable development of the oil and gas business without causing harm to the environment Wednesday.